2018
DOI: 10.3390/molecules23112956
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Comparison of Rosmarinic Acid and Carnosic Acid in Primary Cultures of Cerebellar Granule Neurons

Abstract: Neurodegenerative disorders such as amyotrophic lateral sclerosis (ALS), Alzheimer’s disease, and Parkinson’s disease, are characterized by the progressive loss of neurons in specific regions of the brain and/or spinal cord. Neuronal cell loss typically occurs by either apoptotic or necrotic mechanisms. Oxidative stress and nitrosative stress, along with excitotoxicity and caspase activation, have all been implicated as major underlying causes of neuronal cell death. Diverse nutraceuticals (bioactive compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…These results suggest involvement of inhibition of apoptotic and necrotic processes in the neuroprotective action of MC. It should be noted that previous studies demonstrated that CA or its derivatives inhibited apoptotic processes in neuronal cells which were induced by various factors (e.g., low potassium level, H 2 O 2 , serum deprivation) [ 5 , 8 , 13 , 19 , 40 ] and our present results extend these data by showing the effects of MC in the oxidative stress-based model. It is also in line with previous data from non-neuronal cells (kidney epithelium cell line LLC-PK) where MC (100 μM) reduced the contrast-induced caspase-3 activity and increased cell survival [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results suggest involvement of inhibition of apoptotic and necrotic processes in the neuroprotective action of MC. It should be noted that previous studies demonstrated that CA or its derivatives inhibited apoptotic processes in neuronal cells which were induced by various factors (e.g., low potassium level, H 2 O 2 , serum deprivation) [ 5 , 8 , 13 , 19 , 40 ] and our present results extend these data by showing the effects of MC in the oxidative stress-based model. It is also in line with previous data from non-neuronal cells (kidney epithelium cell line LLC-PK) where MC (100 μM) reduced the contrast-induced caspase-3 activity and increased cell survival [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…We rather think that when MC was given 30 min after H 2 O 2 , the cellular damage reached an advanced stage, at which MC was not protective any longer. It should be noted that most previous studies testing neuroprotective potential of CA derivatives usually used pre-treatment protocols (24 h, 2 h, or 1 h before toxin exposure) but without any comparisons between them [ 13 , 19 , 24 , 40 ]. The relatively narrow time window of MC efficacy (the best effects in pre-treatment group, slightly worsened in co-treatment group and lack of effect in post-treatment group) found in our study suggests that it might be mainly recommended for preventive strategy of neuronal damage, but not for reducing already existing brain injury, e.g., in the late phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, evidence shows that prolonged exposure to high concentrations of CORT can induce mitochondrial dysfunction and neuronal apoptosis (Gong, Zhang, Guo, & Fu, 2018; B. Liu et al., 2011; Woo et al., 2018). Additionally, the neuroprotective effect of RA, the main phytochemical content of MO, has been demonstrated in a large body of studies, and is mainly through suppression of oxidative stress and the apoptosis pathway (Cui et al., 2018; Khamse et al., 2018; H. J. Lee et al., 2008; Taram, Ignowski, Duval, & Linseman, 2018). It seems that both the increase in CORT and ROS overproduction could activate apoptotic signalling pathways, which might be ameliorated by MO through relieving the oxidative stress and CORT levels.…”
Section: Discussionmentioning
confidence: 99%